Implikasi Kecerdasan Buatan dalam Aktivitas Manajemen - Hanif, Rizky Fadil (Jurnal Pelita Teknologi, 2023)
This research focuses on the consequences of advances in Artificial Intelligence Systems on management practices in the coming decade. Much of the attention revolves around comparisons between replacement and upgrading in the context of Artificial Intelligence and the world of work. According to previous studies, machine learning tools are not only able to replace certain tasks, but can also complement human decision-making capabilities. Based on interviews with semi-structured experts, the study provides an early indication that this may be especially true for managers at the top levels of organizations. However, operational and middle managers may experience a more limited impact, with the possibility that most of their tasks can be replaced. As routine supervisory and administrative tasks are automated, there appears to be a shift toward focusing on interpersonal leadership tasks for many managers. There are two future scenarios that can be illustrated to illustrate the impact of Artificial Intelligence on management. On the other hand, the role of algorithmic management is recognized as a crucial element in the coming decade, especially with the continued growth in the platform economy. Given its potential in replacing operational manager duties, further research into the fairness of algorithmic management becomes a must.